Fusion Rate of Subtalar Arthrodesis in Pre-Existing Ankle Arthrodesis: Is There Enough Evidence. Issue 1 (January 2022) - Elhassan, Yahya; Jamjoom, Ammer; Lomax, Adam; Tellisi, Nazzar
Category: Hindfoot Introduction/Purpose: Isolated subtalar arthrodesis is a commonly performed procedure, which produces high union rates. It was suggested that the fusion rate of subtalar arthrodesis is negatively affected by the presence of pre-existing ipsilateral ankle (tibiotalar) arthrodesis, though the mechanism by which this occurs remains unclear. The aim of this study is to assess the fusion rate of subtalar arthrodesis in the presence of pre-existing ipsilateral ankle arthrodesis and to suggest alternative techniques to improve fusion rate. Methods: Electronic patient records and images of all consecutive isolated primary subtalar arthrodesis that were performed in our institution over ten years between (2009-2019) were retrospectively reviewed. Data that was collected included patients' demographics, body mass index (BMI), smoking status, diabetes, and rheumatoid arthritis, fusion rate; other factors like the method used of the pre-existing ankle arthrodesis were also studied. Subtalar arthrodesis was performed using a lateral approach and compressed by two screws. Two groups were compared, included all isolated primary subtalar arthrodesis with or without previous ipsilateral ankle arthrodesis. Logistic regression was performed to check for the correlation between fusion rate and all factors. Results: A total of one hundred and thirty-three (n=133) primary isolated subtalar arthrodesis were identified between (2009- 2019), amongst which twenty-one (n=21) had pre-existing ipsilateral ankle arthrodesis. Ten (n=10) recorded subtalar non-unions occurred in the pre-existing ankle arthrodesis group representing a fusion rate of only 52.4 %, as opposed to sixteen (n=16) in the isolated subtalar fusion without pre-existing ipsilateral ankle arthrodesis group representing a fusion rate of 86.9 %. A significant statistical difference between the two groups, those with ipsilateral ankle arthrodesis had a higher non-rate (P =.001). Age, gender, Body mass index (BMI), smoking status, diabetes, rheumatoid arthritis, and the method used of the pre-existing ankle arthrodesis were found not to have any significant effect on these results. Conclusion: Our results show a significantly higher non-union rate of isolated subtalar arthrodesis in the presence of pre-existing ipsilateral ankle arthrodesis. Further research is required to help in clarifying the mechanism by which this effect occurs and to study alternative surgical techniques that might be required.